2020
DOI: 10.21776/ub.jsal.2020.007.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Modifikasi Unit Proses dalam Peningkatan Efisiensi Penyisihan Amonium

Abstract: Saat ini kualitas badan air semakin menurun akibat pembuangan limbah domestik dan industri secara langsung pada aliran sungai. Kualitas air sungai dengan beban nutrien dan organik yang tinggi mempersulit pengolahan air minum di salah satu industri DKI Jakarta. Salah satu dampak dari memburuknya beban nutrien air baku adalah tingginya kandungan parameter amonium yang berakibat tidak efisiennya proses klorinasi. Hal ini membuat dibangunnya unit MBBR aerob, dengan tujuan menyisihkan kandungan amonium. Akan tetapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The wastewater system uses a waste stabilization pond (WSP) system with high nutrients. However, the high nutrient can cause algae bloom, which reduces water quality (Suryawan et al, 2019;Apritama et al, 2020;Fadhilah et al, 2020). The results of this study showed that there were 37 types of algae with a total suspended solids (TSS) of 611 mg/L (Pratiwi et al 2019).…”
Section: Cultivation and Potential Wastewater Treatmentmentioning
confidence: 87%
“…The wastewater system uses a waste stabilization pond (WSP) system with high nutrients. However, the high nutrient can cause algae bloom, which reduces water quality (Suryawan et al, 2019;Apritama et al, 2020;Fadhilah et al, 2020). The results of this study showed that there were 37 types of algae with a total suspended solids (TSS) of 611 mg/L (Pratiwi et al 2019).…”
Section: Cultivation and Potential Wastewater Treatmentmentioning
confidence: 87%
“…Water recovery can reduce tap water consumption for gardening by about 65.41% (Susana, 2012). Many wastewater treatment designs currently fail to meet quality standards for watering plants and need advanced treatment to improve quality standards (Suryawan et al, 2021;Hasnaningrum et al, 2021;Fadhilah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, humans need eight glasses or 2 liters of drinking water per day so that the body's metabolism goes well (Jami'ah & Hadi, 2014). The total amount of water needed will continue to increase and the increasing number of people will give environmental impact (Sofiyah et al, 2021;Fadhilah et al, 2020;Afifah et al, 2020). If this happens, then what is threatened is the availability of drinking water itself, but it will also impact increasing the generation of plastic bottle waste.…”
Section: Introductionmentioning
confidence: 99%